Digital Green Finance for Sustainable Urban Development - Arniwita; Rahmi Handayani; Ermaini (PT ARRUS Intelektual Indonesia, 2026)
The fast-paced urbanization process and the increased demand for sustainable infrastructure development due to climate changes and the degradation of the environment have raised interest in the emergence of sustainable financial technologies for urban areas. There is a lot of scientific literature available on the subject of green finance and smart cities; however, very little research has been done on the intersection of all these aspects combined – digital financial technologies, ESG investments, environment sustainability indicators, and artificial intelligence – to create a sustainable urban development evaluation framework. This study focuses on the creation of an Intelligent Decision Support System based on Digital Green Finance and its influence on Sustainable Urban Development using quantitative methodology. Mainly, this means using indicators such as green investments' portion in the total sum of investments in a city, ESG financing index, volume of transactions, amount of carbon financing, fintech for sustainable urban development, Green Open Spaces accessibility, urban vegetation index, CO2 emission reduction, urban livability index, and economic resilience. Combining all these factors with SAW-based algorithm and Artificial Intelligence prediction using the Random Forest method enables researchers to assess sustainability rankings and the level of smartness of cities using the developed system. As a result, it is possible to conclude that cities with higher green investment allocation and better ESG financing and digital green transaction volumes are more sustainable. Specifically, Gamma City received the highest ranking, followed by Omega and Alpha Cities.